Regulatory T cells in kidney transplant recipients: the effect of induction immunosuppression therapy - Krystufkova, Eva; Sekerkova, Alena; Striz, Ilja; Brabcova, Irena; Girmanova, Eva; Viklicky, Ondrej (Nephrology, dialysis, transplantation, 2012)
BACKGROUND: Regulatory T cells have been suggested to down-regulate the alloimmune response. The aim of this prospective open study was to evaluate the effects of different inductive agents on peripheral blood regulatory T cells in kidney transplant patients and to analyse their association with short-term graft outcome. METHODS: Regulatory and effector T cell numbers in peripheral blood were determined by flow cytometry in 71 prospectively followed kidney transplant recipients at postoperative day 0, 7, 14, 21, 28, 60 and 90. Patients were treated with a calcineurin inhibitor-based triple immunosuppression with polyclonal rabbit anti-thymocyte globulin (rATG, n = 28), basiliximab, the anti-CD25 monoclonal antibody (n = 18) or without induction (controls, n = 25). Flow cytometry data were correlated to rejection incidence. RESULTS: Compared to controls, CD4(+)CD25(+)FoxP3(+) regulatory T-cell expansion among CD4(+) T cells was noticed in the rATG group at all post-transplant time-points by Day 14 (P < 0.001). A significant decrease in Treg frequency (P < 0.001) and concurrently a transient increase of CD4(+)CD25(low/-)FoxP3(+) population were observed in basiliximab-treated patients 7-60 days post-transplantation. Biopsy-proven acute rejection occurred in 16.7% of controls, 10.7% of the rATG group and in 11.1% of the basiliximab group. Higher CD4(+)FoxP3(+)/CD8(+)CD45RA(+)CD62L(-) ratios were observed repeatedly in those patients after basiliximab induction who were rejection free (P < 0.01). CONCLUSIONS: In this study, the rATG induction therapy was associated with an expansion of regulatory cells. Sustained high CD4(+)FoxP3(+)/Teff ratios were associated with the absence of rejection after basiliximab induction.
Keywords: senioři; basiliximab; rejekce štěpu; Immunosuppressive Agents; průtoková cytometrie; imunologická tolerance; transplantace ledvin; Prognosis; mladiství; monoklonální protilátky; Middle Aged; mužské pohlaví; regulační T-lymfocyty; Antibodies, Monoclonal; Prospective Studies; Adult; mladý dospělý; antilymfocytární sérum; receptor interleukinu-2 - alfa-podjednotka; Follow-Up Studies; imunosupresivní léčba; Flow Cytometry; následné studie; T-Lymphocytes, Regulatory; Young Adult; ženské pohlaví; prognóza; Kidney Transplantation; Graft Rejection; imunosupresiva; prospektivní studie; Humans; Recombinant Fusion Proteins; rekombinantní fúzní proteiny; lidé středního věku; Immune Tolerance; Immunosuppression Therapy; Interleukin-2 Receptor alpha Subunit; Antilymphocyte Serum; dospělí; Female; Aged; Adolescent; Basiliximab; lidé; Male